Associations between genetic variation in one-carbon metabolism and leukocyte DNA methylation in valproate-treated patients with epilepsy. Issue 1 (February 2018) - Ni, Guanzhong; Qin, Jiaming; Chen, Ziyi; Li, Hongliang; Zhou, Jueqian; Huang, Min; Zhou, Liemin
Summary: Background: Valproate (VPA) as a first-line antiepileptic drug is useful for the most types of epileptic seizure treatment. Previous studies observed that VPA influenced one-carbon metabolism (OCM), consequently, DNA methylation. However, other individual genetic variations, as well as VPA, modify DNA methylation. Objective: In this study, we investigated associations between genetic variations in OCM and leukocyte DNA methylation in VPA-treated patients with epilepsy. Methods: This was a cross-sectional study of 101 epileptic patients who underwent VPA monotherapy and 68 healthy controls. All subjects were measured OCM-related nutrients (folate, homocysteine and vitamin B12), and DNA methylation of specific regions were analyzed. Furthermore, we examined the associations between genetic variations in OCM and DNA methylation levels in epileptic patients. Results: VPA-treated patients with epilepsy exhibited both higher serum homocysteine and vitaminB12 levels and lower folate levels relative to controls ( P  = 0.018, P  = 0.003, P  < 0.001 respectively), the methylation level of the MTHFR amplicon was significantly lower in the VPA group compared with those in the controls ( P  = 0.043). VPA-treated epileptic patients carrying the T-allele of methylenetetrahydrofolate reductase (MTHFR) c.677C>T showed higher serum Hcy levels than those observed in the 677CC group ( P  < 0.01). Epileptic patients who carried G-allele of methionine synthase (MTR) c.2756A>G showed significantly lower MTHFR amplicon methylation levels compared to carriers of the wild-type MTR 2756AA genotype ( P  = 0.028). Conclusion: Our study provided evidence that the MTR c.2756A>G polymorphism is associated with MTHFR amplicon hypomethylation in VPA-treated patients with epilepsy.